Healthy Workplace Practices for Enhancing Employee Performance: A Case Study of Chinese Hot Pot Enterprise - Sicheng Li; Jirapong Ruanggoon (Journal of Human Resource Management)
Purpose – This paper addressed the gap in research on healthy workplace practices in Chinese hot pot enterprises, particularly focusing on their impact on employee performance. The existing literature rarely explored this context, and this study aimed to fill that gap by providing industry-specific insights and practical recommendations for improving employee performance in Chinese food service settings. Aims(s) – The primary aim was to examine the effects of healthy workplace practices on employee performance within a Chinese hot pot enterprise. The secondary aim was to propose initiatives to enhance employee performance. Design/methodology/approach – The study employed quantitative methods to achieve its research objectives. Data were collected through a structured questionnaire administered to a random sample of 500 employees from 52 Chinese hot pot stores in Nanjing. Descriptive statistics were used to summarize the data, and structural equation modeling (SEM) was applied to analyze the relationships between healthy workplace practices and employee performance. Additionally, three industry experts evaluated and validated the proposed initiatives aimed at improving employee performance. This expert validation ensured the relevance and practicality of the recommendations for the industry. Findings – The study found that healthy workplace practices—particularly work-life balance, employee growth and development, health and safety, and employee involvement—significantly improved employee performance in Chinese hot pot enterprises. Among these, work-life balance was the most influential factor, with each practice positively affecting both task and contextual performance. The study also proposed initiatives to further enhance employee performance, including flexible scheduling, increased access to training and career development, improved health resources, and better feedback systems. Limitations of the study – The study was limited to Nanjing, and future research could expand the sample to other regions and incorporate qualitative methods for deeper insight. Originality/value – This paper provided new insights into healthy workplace practices in the Chinese hot pot industry, offering valuable recommendations for HR professionals and managers to improve employee performance.